The Power of Words: Bias and Assumptions in the Aboriginal and Torres Strait Islander Education Action Plan - Melitta Hogarth (The Australian Journal of Indigenous Education, 2017)
This paper argues that genuine engagement and consultation is required where Indigenous voice is prevalent within the policy development process for true progress to be achieved in the educational attainments of Aboriginal and Torres Strait Islander students. It is important to note that there has been little critical analysis of policy discourses. More specifically, analysis of how language is used to maintain societal constructs. By providing an Indigenous standpoint, it is anticipated that this paper makes explicit to policymakers the bias and taken for granted assumptions held by those who produced it. This paper is derived from a larger project, namely my Masters of Education (Research) thesis (Hogarth, 2015). The major findings that emerged from the data included (a) the homogenous grouping of Aboriginal and Torres Strait Islander people, (b) the maintenance of the prevalent dominant ideology of a deficit view within policy and finally (c) the expectation of government of increased engagement and connections with and by Aboriginal and Torres Strait Islander peoples in education without consideration of the detrimental effects of past policies and reforms. The potential implications of making explicit how language positions Aboriginal and Torres Strait Islander students’ educational attainment can inform future policymaking and contribute to the struggle for self-determination.